Between Poetic Voice and Silence: Hart Crane, Yvor Winters, Metapoetics and Emily Dickinson’s Legacy - Piechucka, Alicja (Text Matters: A Journal of Literature, Theory and Culture, 2020)
The article is a comparative study of the ways in which two American modernist poets bound by a literary and human connection, Hart Crane and Yvor Winters, dealt with Emily Dickinson’s legacy in their own works. My study is an attempt to place Crane within the legacy of the American Renaissance as represented not by Walt Whitman, with whom he is customarily associated, but by Dickinson, and to examine the special place she holds in Crane’s poetry and in his thinking about poetry and the world at large. Crane’s poetic take on the Amherst poet is set against and complemented by his friend Yvor Winters’s ambiguous relationship with Dickinson’s heritage: troubled by an anxiety of influence, Winters, the poet-critic, vacillates between his reverence for the female poet and his skepticism about certain aspects of her œuvre. In the close readings of the poems in question undertaken in my study, the focus is on their metapoetic dimension. Particular emphasis is laid on the dialectics of silence, which plays a key role in both Crane’s and Winters’s works under discussion, as well as on the related themes of blankness and absence, poetic plenitude and perfection. Attention is also given to the problematics of death, time and timelessness. While Winters concentrates mostly on metapoetics in his exploration of the Dickinsonian tradition, Crane goes further, considering the fate of female artists and gender issues, thereby transcending poetic self-reflexiveness and addressing farther-reaching community concerns, with particular emphasis on anti-patriarchal and feminist ones.